Distressed to Distracted: Examining Undergraduate Learning and Stress Regulation During the COVID-19 Pandemic. (December 2021) - Mesghina, Almaz; Wong, Joseph T.; Davis, Elizabeth L.; Lerner, Bella S.; Jackson-Green, Bryant J.; Richland, Lindsey E.
Undergraduates' distress has increased dramatically since the COVID-19 pandemic's onset, raising concerns for academic achievement. Yet little is known about the mechanisms by which pandemic-related distress may affect students' learning and performance, and consequently, how we might intervene to promote student achievement despite the continuing crisis. Across two studies with nearly 700 undergraduates, we highlight the mediating role of distraction: undergraduates higher in COVID-19 distress saw lower learning gains from an asynchronous neuroscience lesson due to increased mind wandering during the lesson. We replicate and extend this finding in Study 2: probing what pandemic-related stressors worried students and revealing systematic differences among students of marginalized identities, with largest impacts on first-generation, Latinx women. We also examined whether stress reappraisal or mindfulness practices may mitigate the observed distress-to-distraction pathway. Only mindfulness reduced mind wandering, though this did not translate to learning. We conclude with implications for practice and future research.